Is functional fitness performance a useful predictor of risk of falls among community-dwelling older adults? - Hsin-Hung Ho; I-Yao Fang; Yi-Chien Yu; Yi-Ping Huang; I-Ling Kuo; Li-Ting Wang; Ming-Chueh Tsai; Shao-Hsi Chang; Ming-Chun Hsueh (BMC, 2021)
Abstract Background Falls among older adults are a serious public health problem. Many studies indicate that positive functional fitness performance decreases the risk of falls. A limited amount of previous study has investigated the association between broad functional fitness and the fall risk. This study examines the associations between functional fitness and the risk of falling among community-dwelling older adults. Methods Three waves of cross-sectional data were collected from 2017 to 2019 in Taipei City, Taiwan. Six hundred sixty-five participants aged ≥65 years were randomly recruited from 12 districts of Taipei. Eight functional fitness tests (i.e., back scratch, chair-sit and-reach, 8-ft up-and-go, 30-s sit-to-stand, 30-s arm curl, 30-s single-leg stance, 2-min step, and hand grip strength tests) were performed to record the physical performance of older subjects. A Chinese version of the fall-risk questionnaire (FRQ) was used to calculate the fall risk scores. Linear regression and logistic regression were utilized to estimate the relationships of each functional fitness and fall risk. Result The results showed that 37.45% of older adults had a high risk of falling. It was found for each functional fitness that performance was linearly associated with the risk of falling. Moreover, older adults with low-performance levels in all functional fitness except back-scratching were more likely to have a higher risk of falling. Conclusions Our study indicated that functional fitness performance appears to provide valid predictive guidance for reducing the risk of falling among the older population.